Transforming Workplace Learning: A Qualitative Inquiry into Adopting Massive Open Online Courses into Corporate Learning and Development - Agnieszka Żur; Christian Friedl (MDPI AG, 2021)
Despite the wide acknowledgement of the knowledge-based economy, the need for life-long learning and quickly growing open online resources, Massive Open Online Courses (MOOCs) are not common means of corporate learning and development programs. The aim of this study is to identify key factors determining the adoption of MOOCs in corporate workplace learning programs. In this exploratory research, the authors employ empirical data from 36 in-depth interviews with corporate managers directly responsible for learning and development practices. Findings provide potential explanations for the mismatch between a generally positive attitude towards MOOCs and their still low adoption rate by identifying expectations towards MOOCs, as well as major reservations. We find that while corporations recognize the opportunities MOOCs can introduce into workplace learning, elevated expectations, negative first-time experiences and objective barriers inhibit MOOC adoption in corporate learning and development programs. It is among the first to expose the perspective of organizations at an early stage of adopting MOOCs. The findings provide a novel contribution to both workplace learning scholarship as well as practical recommendations which can inform HR managers' decisions in regard to adopting digital means in workplace learning.